1994
DOI: 10.1002/dvg.1020150111
|View full text |Cite
|
Sign up to set email alerts
|

Diverse programs of ascus development in pseudohomothallic species of Neurospora, Gelasinospora, and Podospora

Abstract: Meiosis and ascospore development in the four-spored pseudohomothallic ascomycetes Neurospora tetrasperma, Gelasinospora tetrasperma, Podospora anserina, and P. tetraspora have been reexamined, highlighting differences that reflect independent origins of the four-spored condition in the different genera. In these species, as in the heterothallic eight-spored N. crassa, fusion of haploid nuclei is followed directly by meiosis and a postmeiotic mitosis. These divisions take place within a single unpartitioned gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
106
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 43 publications
2
106
0
1
Order By: Relevance
“…Neurospora crassa (Herskowitz, 1988;Davis, 2000;Metzenberg and Glass, 1990), Podospora anserina (Zickler et al, 1995;Coppin et al, 1997;Raju and Perkins, 1994), Schizosaccharomyces pombe (Herskowitz, 1988;Kelly et al, 1988) and Ustilago maydis (Kahmann et al, 1995;Martinez-Espinosa et al, 1993), so that mating between individuals can be controlled. Development of the genetic system of S. cerevisiae has largely depended on the inactivation of HO so that strains are functionally heterothallic, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Neurospora crassa (Herskowitz, 1988;Davis, 2000;Metzenberg and Glass, 1990), Podospora anserina (Zickler et al, 1995;Coppin et al, 1997;Raju and Perkins, 1994), Schizosaccharomyces pombe (Herskowitz, 1988;Kelly et al, 1988) and Ustilago maydis (Kahmann et al, 1995;Martinez-Espinosa et al, 1993), so that mating between individuals can be controlled. Development of the genetic system of S. cerevisiae has largely depended on the inactivation of HO so that strains are functionally heterothallic, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of nuclear mixing, mathematical modeling showed that heterokaryotic thalli should often break down into homokaryons (Roper et al 2013). Pseudohomothallic Ascomycota, such as Podospora anserina and Neurospora tetrasperma, produce mat+/mat2 (or mat A/mat a) dikaryotic ascospores, which upon germination yield a self-fertile heterokaryotic mycelium (Raju and Perkins 1994). In addition to being able to engage in selfreproduction, this mycelium is also able to mate with any partner it may encounter.…”
mentioning
confidence: 99%
“…The filamentous ascomycete N. tetrasperma is a self-fertile (pseudohomothallic) organism presumed to have evolved from a self-incompatible (heterothallic) ancestor (15,50). As with most filamentous ascomycetes, the N. tetrasperma mat chromosomes contain the mat locus, which comprises two dissimilar alleles (mat a and mat A idiomorphs) that regulate mating and sexual reproduction (10,53).…”
mentioning
confidence: 99%